2022
DOI: 10.1038/s41467-022-32631-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing sensitivity of dryland vegetation greenness to precipitation due to rising atmospheric CO2

Abstract: Water availability plays a critical role in shaping terrestrial ecosystems, particularly in low- and mid-latitude regions. The sensitivity of vegetation growth to precipitation strongly regulates global vegetation dynamics and their responses to drought, yet sensitivity changes in response to climate change remain poorly understood. Here we use long-term satellite observations combined with a dynamic statistical learning approach to examine changes in the sensitivity of vegetation greenness to precipitation ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 70 publications
1
59
1
Order By: Relevance
“…The results suggested that the reduction in US GPP by TIO warming may be mainly attributed to less precipitation rather than higher temperature. It is also consistent with previous studies, which showed that vegetation activities over the US are mainly dependent on precipitation rather than temperature 22,23,24,25,26,27,28 .…”
Section: Impact Of the Tropical Indian Ocean On Climate Over North Am...supporting
confidence: 93%
“…The results suggested that the reduction in US GPP by TIO warming may be mainly attributed to less precipitation rather than higher temperature. It is also consistent with previous studies, which showed that vegetation activities over the US are mainly dependent on precipitation rather than temperature 22,23,24,25,26,27,28 .…”
Section: Impact Of the Tropical Indian Ocean On Climate Over North Am...supporting
confidence: 93%
“…CO 2 played the most important role in the θ SM increase, which is consistent with its fertilization effect on vegetation. Several studies have indicated that elevated CO 2 causes vegetation to conserve water so that limited water supports more plant growth in water-limited regions (Zhang et al, 2022). This also explained the decrease in the soil moisture with the increase in the NDVI, which was due to the increase in the global CO 2 concentration.…”
Section: Discussionmentioning
confidence: 98%
“…It would offset the effort of rising CO 2 in saving water and constraining photosynthesis in turn. The offset effect was proven to be more serious in semiarid and arid areas (Ukkola et al., 2016; Y. Zhang et al., 2022). This probably explains why drier northwestern China benefits less from rising CO 2 than northeastern China (Figures S10 and S13 in Supporting Information S1).…”
Section: Discussionmentioning
confidence: 99%